Enamel and dentine demineralization by a combination of starch and sucrose in a biofilm - caries model - Juliana Nunes BOTELHO; Mario VILLEGAS-SALINAS; Pía TRONCOSO-GAJARDO; Rodrigo Andrés GIACAMAN; Jaime Aparecido CURY (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract Sucrose is the most cariogenic dietary carbohydrate and starch is considered non-cariogenic for enamel and moderately cariogenic for dentine. However, the cariogenicity of the combination of starch and sucrose remains unclear. The aim of this study was to evaluate the effect of this combination on Streptococcus mutans biofilm composition and enamel and dentine demineralization. Biofilms of S. mutans UA159 were grown on saliva-coated enamel and dentine slabs in culture medium containing 10% saliva. They were exposed (8 times/day) to one of the following treatments: 0.9% NaCl (negative control), 1% starch, 10% sucrose, or 1% starch and 10% sucrose (starch + sucrose). To simulate the effect of human salivary amylase on the starch metabolization, the biofilms were pretreated with saliva before each treatment and saliva was also added to the culture medium. Acidogenicity of the biofilm was estimated by evaluating (2 times/day) the culture medium pH. After 4 (dentine) or 5 (enamel) days of growth, biofilms (n = 9) were individually collected, and the biomass, viable microorganism count, and polysaccharide content were quantified. Dentine and enamel demineralization was assessed by determining the percentage of surface hardness loss. Biofilms exposed to starch + sucrose were more acidogenic and caused higher demineralization (p < 0.0001) on either enamel or dentine than those exposed to each carbohydrate alone. The findings suggest that starch increases the cariogenic potential of sucrose.